The treatment of risk and uncertainty in the US social cost of carbon for regulatory impact analysis - Simon Dietz (Kiel Institute for the World Economy (IfW), 2011)
This note considers the treatment of risk and uncertainty in the recently established social cost of carbon (SCC) for analysis of federal regulations in the United States. It argues that the analysis of the US Interagency Working Group on Social Cost of Carbon did not go far enough into the tail of low-probability, high-impact scenarios, and, via its approach to discounting, it mis-estimated climate risk, possibly hugely. Given the uncertainty about estimating the SCC, the note concludes by arguing that there is in fact much to commend an approach whereby a quantitative, long-term emissions target is chosen, and the price of carbon for regulatory impact analysis is then based on estimates of the marginal cost of abatement to achieve that very target.
Keywords: Q54; 330; Ambiguity; climate change; discounting; integrated assessment modelling; risk; social cost of carbon; uncertainty; Klimaveränderung; Kohlendioxid; Soziale Kosten; Abzinsung; Risiko; USA